On weather signs - Theophrastus (Brill, 2007)
Takes an account of various manuscripts and places the work in its historical and scientific context. This work also lays out the details of the manuscript tradition.
Keywords: Théophraste. -- Des signes.; Weather forecasting -- Early works to 1800.; Meteorology -- Early works to 1800.; Temps (Météorologie) -- Prévision -- Ouvrages avant 1800.; Météorologie -- Ouvrages avant 1800.; NATURE -- Weather.; SCIENCE -- Earth Sciences -- Meteorology & Climatology.; Meteorology; Weather forecasting; Weersverwachtingen.; Early works